Online Learning as a Teaching And Learning Activities Alternative in The COVID-19 Pandemic - Ade Kurniawan Kurniawan; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
The purpose of this study was to determine the implementation of online learning during the COVID-19 pandemic. This online learning was carried out due to the outbreak of the coronavirus 19. The sample of this research was elementary, middle, and private high school students in Lampung. This study uses a simple random sampling technique by considering the homogeneity of the population. The data instrument uses an online learning questionnaire. Data analysis used descriptive statistics. The results of the study illustrate that the most widely used online learning model is the WhatsApp application at 87.2%, Google Classroom at 41.3%, Google Meeting or Zoom at 13.8%, Youtube at 15.6%, and other applications at 12.8%. This percentage is obtained from respondents who use more than one online learning application.